V tretjem letu delovanja pravne svetovalnice LGBT - Štajnpihler Božič, Tilen (Pravnik, 2017)
The editorial to the special (topical) issue of the journal Pravnik refers to ongoing discussions, among experts as well as in the general public, on the issues of equality and discrimination in our society. In recent years, this discussion has been characterised, inter alia, by the struggle for equal rights of LGBT individuals, couples, and their families. In the editorial, the authors illuminate the active participation of the LGBT legal clinic, i.e. a platform offering law students at the University of Ljubljana an opportunity to use their legal knowledge and expertise in assisting LGBT individuals, couples, and their families in achieving equality, in this discussion. The editorial also outlines the key legal issues related to the Civil Union Act and its practical effects that are further discussed from different perspectives by the students participating in the LGBT legal clinic in their contributions.